Voluntary food intake by elite female cyclists during training and racing: Influence of daily energy expenditure and body composition - Martin, M. K.; Martin, D. T.; Collier, G. R.; Burke, L. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2002)
We estimated self-reported energy intake (EI) and cycling energy expenditure (CEE) during racing and training over 26 days (9 days recovery [REC], 9 days training [TRN], and 8 days racing [RACE], which included a 5-day stage race) for 8 members of the Australian National Training Squad [mean ± SD; 25.1 ± 4.0 years, 59.2 ± 4.4 kg, 3.74 ± 0.24 L min-1 VO2peak, 13.6 ± 4.5 % Body fat (%Bfat)]. After 70 days of training and racing, average body mass increased by 1.1 kg (95%CI 0.5 to 1.7 kg; p < .01) and average %Bfat decreased by 0.9% (95%CI Ð1.7 to Ð0.1%; p < .05). These minor changes, however, were not considered clinically significant. CEE was different between RACE, TRN, and REC (2.15 ± 0.18 vs. 1.73 ± 0.25 vs. 0.72 ± 0.15 MJ d-1, p < .05). Reported EI for RACE and TRN were higher than REC (14.87 ± 3.03, 13.70 ± 4.04 vs. 11.98 ± 3.57 MJ d-1, p < .05). Reported intake of carbohydrate for RACE and TRN were also higher than REC (588 ± 122, 536 ± 130 vs. 448 ± 138 g d-1, p < .05). Reported intake of fat (59 ± 21Ð68 ± 21 g d-1) was similar during RACE, TRN, and REC, whereas protein intake tended to be higher during TRN (158 ± 49 g d-1) compared to RACE and REC (136 ± 33; 130 ± 33 g d-1). There was a relationship between average CEE and average EI over the 26 days (r = 0.77, p < .05), but correlations between CEE and EI for each of the women varied (r = Ð0.02 to 0.67). There was a strong trend for an inverse relationship between average EI and %Bfat (r = -.68, p = .06, n = 8). In this study, increases in reported EI during heavy training and racing were the result of an increase in carbohydrate intake. Most but not all cyclists modulated EI based on CEE. Research is required to determine whether physiological or psychological factors are primarily responsible for the observed relationship between CEE and EI and also the inverse correlation between %Bfat and EI.